2015
DOI: 10.1007/s11136-015-1059-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of untreated dental caries and its clinical consequences on the oral health-related quality of life of schoolchildren aged 8–10 years

Abstract: Untreated dental caries and its clinical consequences exerted a negative impact on the OHRQoL of the schoolchildren analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
91
5
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(107 citation statements)
references
References 25 publications
3
91
5
8
Order By: Relevance
“…The authors found that all domains of quality of life were negatively affected by individuals with a higher severity of caries lesions, and the oral health-related quality of life score was 33% higher for adolescents with untreated caries lesions [Feldens et al 2016]. Another study presented similar data, the results of which showed that the presence of dental caries increased the frequency of negative impact on emotional well-being by 29% and on social wellbeing by 61% in the quality of life domains [Mota-Veloso et al, 2016].…”
Section: Discussionmentioning
confidence: 84%
“…The authors found that all domains of quality of life were negatively affected by individuals with a higher severity of caries lesions, and the oral health-related quality of life score was 33% higher for adolescents with untreated caries lesions [Feldens et al 2016]. Another study presented similar data, the results of which showed that the presence of dental caries increased the frequency of negative impact on emotional well-being by 29% and on social wellbeing by 61% in the quality of life domains [Mota-Veloso et al, 2016].…”
Section: Discussionmentioning
confidence: 84%
“…6,7,8,12,13,14,21,24 Moreover, our results bring new evidence of the long-term effects of caries treatment on the OHRQoL of schoolchildren aged 8 to 10 years. Although other studies have demonstrated improvements in children's OHRQoL after dental treatment, they generally have focused on outcomes in younger children using the Early Childhood Oral Health Impact Scale (ECOHIS), Child-Oral Impacts on Daily Performances (Child-OIDP), the Parental-Caregivers Perception Questionnaire (P-CPQ), 17,25,26,27 and research in which treatment was proposed for early childhood caries under general anesthesia.…”
Section: Discussionmentioning
confidence: 58%
“…3,4 Children and adolescents worldwide suffer from diverse oral problems, but dental caries remains the most prevalent oral disease, which is mediated by psychosocial determinants and has severe consequences for OHRQoL, happiness, and school performance. 5,6,7,8,9 Even though studies with this population have investigated the impact of OHRQoL related to orthodontic treatment, oral rehabilitation under general anesthesia, Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Essa doença causa sintomatologia dolorosa e alterações na linguagem oral (15) missing, and filled teeth--D-DMFT in permanent teeth or d-dfmt in primary teeth, assim como impacta a qualidade de vida e a percepção estética, devido aos sinais e sintomas apresentados, como observado no presente estudo.…”
Section: Discussionunclassified